Norm Values and Psychometric Properties of the 24-Item Demoralization Scale (DS-I) in a Representative Sample of the German General Population - Quintero Garzón, Leonhard; Hinz, Andreas; Koranyi, Susan; Mehnert-Theuerkauf, Anja (Frontiers in Psychology, 2021)
Purpose: The Demoralization scale (DS-I) is a validated and frequently used instrument to assess existential distress in patients with cancer and other severe medical illness. The purpose of this study was to provide normative values derived from a representative German general population sample and to analyze the correlational structure of the DS-I. Methods: A representative sample of the adult German general population completed the DS-I (24 Items), the Emotion Thermometers (ET) measuring distress, anxiety, depression, anger, need for help, and the Functional Assessment of Chronic Illness Therapy Fatigue Scale (FACIT-fatigue). Results: The sample consists of N = 2407 adults (mean age = 49.8; range = 18 - 94 years), 55.7% women). The percentages of participants above the DS-I cutoff (≥ 30) was 13.5%. The mean scores of the DS-I dimensions were as follows: (1) loss of meaning and purpose: M = 2.78 SD = 4.49; (2) disheartenment: M = 3.19 SD = 4.03; (3) dysphoria M = 4.51 SD = 3.20; (4) sense of failure: M = 6.24 SD = 3.40; and for the DS-I total score: M = 16.72 SD = 12.74. Women reported significantly higher levels of demoralization than men, with effect sizes between d = .09 (Loss of Meaning) and d = .21 (Dysphoria). Age was not associated with demoralization in our sample. DS-I reliability was excellent (α = .94) and DS-I subscales were interrelated (r between 0.31 and 0.87) and significantly correlated with ET, especially depression, anxiety and need for help and fatigue (r between 0.14 and 0.69). Conclusions: In order to use the DS-I as a screening tool in clinical practice and research the normative values are essential for comparing the symptom burden of groups of patients within the health care system to the general population. Age and sex differences between groups of patients can be accounted for using the presented normative scores of the DS-I.